Analiza i modeliranje očvršćivanja poliesterskih smola u valjkastim kalupima grijanim zrakom - Marečić, Miroslav (Array, 2009)
Summary: The mathematical model of the cure of unsaturated polyester resin in cylindrical mould heated with warm air was suggested and derived. The model assumes convective heat transfer through air on the wall of the mould and conductive heat transfer through the resin. The temperature within the sample changes during the cure process, which is the result of the reaction being exothermal and the process of heat transfer. The addition of the filler changes the thermal properties of the mixture and reduces the amount of heat generated during the reaction in the sample of the same volume, which leads to lower temperature maximums in the center of the cylindrical mould. The model was tested with multiple experiments in which the temperature of the resin inside the mould during the cure process was measured. The heat transfer coefficients between the air and wall of the mould with different speeds of air flow were estimated using independent experiments where the glycerol was used instead of resin. Estimated values were compared with known correlations and good agreement was obtained. Using the suggested model, the cure process in the cylindrical mould can be simulated accurately and influents of the heat transfer and reaction rate on the temperature maximums can be studied